Model of Blue Ocean Strategy Developing a Bamboo Small Business in Medan City - Samrin; Hasrul Azwar Hasibuan; Rahmat Hidayat; Rusiadi (CERED Indonesia Institute, 2022)
The research objective is to analyze the Blue Oceans Strategy method approach to improve strategy development for the Small and Medium Bamboo Industry in Medan City. Woven crafts are one of the most abundant businesses in the SME sector, both rattan and bamboo handicrafts have dominated the activities of SMEs in Medan City . The woven crafts are spread in 5 (five) sub-districts in Medan City. The method of analysis in this study uses a Structural Equation Modeling (SEM) approach, in forming a strategy for developing SMEs and Bamboo cooperatives with the ocean strategy and blue ocean strategy models in Medan City. The competitive strategy used by the Small and Medium Shell Industry in Medan City at this time is to identify competitive factors in the industry which consist of product uniqueness, a touch of art, done in detail, proximity to sources of raw materials, strategic location, availability of labor, Creativity, Prices are not fixed on market prices, Can be used as souvenirs, Skills and skills of employees, Attractiveness and impact after participating in exhibitions, Sensitivity to market choices, Organizational commitment, Work environment, Availability of online order facilities, Experience and managerial skills, Product orders completed on time.